2018
DOI: 10.1186/s13012-018-0763-4
|View full text |Cite
|
Sign up to set email alerts
|

The advantages and limitations of guideline adaptation frameworks

Abstract: BackgroundThe implementation of evidence-based guidelines can improve clinical and public health outcomes by helping health professionals practice in the most effective manner, as well as assisting policy-makers in designing optimal programs. Adaptation of a guideline to suit the context in which it is intended to be applied can be a key step in the implementation process. Without taking the local context into account, certain interventions recommended in evidence-based guidelines may be infeasible under local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(123 citation statements)
references
References 31 publications
1
107
0
15
Order By: Relevance
“…lack of consumer understanding, limited space on menus). While adaptation can be viewed as a key step in the implementation process [98,99], the risk of compromising fidelity to core intervention components and potentially reducing the effects needs to be considered [100]. Few of the included studies adequately reported on the intervention components of their menu labelling scheme; thus future studies should report on same using the TIDieR-PHP checklist [101].…”
Section: Implications and Recommendations For Practice Policy And Rmentioning
confidence: 99%
“…lack of consumer understanding, limited space on menus). While adaptation can be viewed as a key step in the implementation process [98,99], the risk of compromising fidelity to core intervention components and potentially reducing the effects needs to be considered [100]. Few of the included studies adequately reported on the intervention components of their menu labelling scheme; thus future studies should report on same using the TIDieR-PHP checklist [101].…”
Section: Implications and Recommendations For Practice Policy And Rmentioning
confidence: 99%
“…We utilised the 'KSU Modi ed ADAPTE' [9] adaptation methodology, a natural evolution of two earlier formal adaptation methodologies for CPGs, the original ADAPTE and 'Adapted ADAPTE' methods [12][13][14], which consists of three phases and 24 steps with modi cations in the steps and tools to suit the local general healthcare setting in Saudi Arabia [9,13]. Figure 1 provides a simpli ed owchart of our methods [9].…”
Section: Guideline Adaptation Methodsologymentioning
confidence: 99%
“…Adaptation of CPGs is a valid and e cient alternative to de novo development of CPGs especially in resourcelimited healthcare settings. It was proposed to avoid duplication of efforts, to use the available resources in a cost-effective manner, and to encourage trans-contextual customization of the CPG prepared for different economic and healthcare settings re ecting the local context and system [9][10][11][12][13].…”
mentioning
confidence: 99%
“…This study aimed to: i) explore researchers' and practitioners' views on adaptation guidance as summarized in two recent scoping reviews by Escoffrey et al (2018) and Wang et al, (2018) [9,10], ii) identify potential improvements to increase the practicality of adaptation frameworks in real world settings and iii) identify future opportunities to advance the adaptation literature to achieve better public health outcomes.…”
Section: Aimsmentioning
confidence: 99%